(untitled) (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Nurhikmayani R, Daryono BS, Retnaningrum E. 2019. Isolation and molecular identification of antimicrobial-producing Lactic Acid Bacteria from chao, South Sulawesi (Indonesia) fermented fish product. Biodiversitas 20: 1063-1068. Chao is traditional fermented fish made of anchovy (Stolephorus sp.), rice, salt, and fermented naturally on controlled environment. The product comes from Pangkep Regency, South Sulawesi. Chao has the potential for the source of high-grade lactic acid bacteria isolates, especially for antimicrobial compound. Antimicrobial compound produced by lactic acid bacteria is a biopreservative compound with many advantages. The purposes of this investigation were to isolate antimicrobial-producing lactic acid bacteria from chao and to identify their isolates based on the molecular properties. Lactic acid bacteria were isolated from chao using Man Ragosa Sharpe Agar (MRSA) medium added with 0.1 % CaCO3, followed by the ability test to produce antimicrobial compound against Staphylococcus aureus FNCC 0047 as an indicator. The spectrum of crude antimicrobial as cell-free supernatant (CFS) was determined by antagonism against S. aureus FNCC 0047 and Escherichia coli FNCC 0049 on agar well diffusion test. Selected isolates of antimicrobial-producing lactic acid bacteria molecularly identified from 16S rRNA marker using primer 27F and 1492R. We obtained four isolates of lactic acid bacteria that showed the antimicrobial activity. This crude antimicrobial compound could inhibit both gram-positive Staphylococcus aureus FNCC0047 and gram-negative bacteria Escherichia coli FNCC0049. The highest crude antimicrobial activity of isolates was observed on IB1C strain. The results of molecular characterization suggested that the IB1C and IB3B strain were identified as Lactobacillus plantarum, whereas IB3E and IB3F were identified as Pediococcus pentosaceus.